Characteristics of depression in community‐dwelling elderly people as indicated by the tree‐drawing test. Issue 4 (24th July 2015) - Murayama, Norio; Endo, Tadashi; Inaki, Koichiro; Sasaki, Shinsai; Fukase, Yuko; Ota, Kazumi; Iseki, Eizo; Tagaya, Hirokuni
Abstract: Background: The tree‐drawing test (TDT) is a typical projective method, but previous studies have paid little attention to it for elderly people. We investigated the characteristics of depression in community‐dwelling elderly people as indicated by the TDT. Methods: This study was a complete enumeration survey of elderly people conducted through home visits. The contents of the survey included gender, age, presence or absence of housemates, frequency of going out, the 15‐item Geriatric Depression Scale, and TDT. The subjects were divided into three groups (normal, depressed tendency, and depressed) according to the total 15‐item Geriatric Depression Scale score. Results: In TDT, no significant difference was observed in drooping crown, shadow of the whole tree, or shadow near the base, which have been regarded as indices of depression in younger people. However, the values concerning the size of the tree, such as the height and width of the whole tree, height and width of the crown, and number of occupied areas (of the paper), were significantly lower in the depressed group than in the other groups. In addition, the width of the trunk was significantly smaller in the depressed group than in the normal group. Subjects were classified as being in a 'depressed state' if they used 40 or fewer areas for drawing (i.e. occupied areas) and a 'non‐depressed state' if they used 41 or more areas. This enabled depression to be detected (sensitivity: 71.4%; specificity: 79.9%). Conclusions: The size of the tree in TDT is suggested to reflect characteristics of depression in elderly people, such as introversion, reserve, antisocial attitude, a feeling of inferiority, weakness of ego, and lack of vigour. Furthermore, the numbers of occupied areas were found to be relatively useful in detecting depression in elderly people.